2007
DOI: 10.1016/j.febslet.2007.01.038
|View full text |Cite
|
Sign up to set email alerts
|

CD14 is a ligand for the integrin α4β1

Abstract: Cell adhesion mediated by the integrin a4b1 plays a key role in many biological processes reflecting both the number and functional significance of a4b1 ligands. The lipopolysaccharide (LPS) receptor, CD14, is a GPI-linked cell surface glycoprotein with a wide range of reported functions and associations, some of which overlap with that of a4b1. This overlap led us to test the specific hypothesis that a4b1 and CD14 interact directly. Jurkat T cells (a4b1 + ) were found to adhere to a recombinant CD14-Fc protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…We show here that CD14-neutralizing antibody attenuates LPSinduced signal transduction in MLE12 cells. Recent studies demonstrated that, in addition to LBP, CD14 interacted with other proteins, such as surfactant A (32), C (2), and D (32), integrin-␤ 1 (22), and Mac-1 (27); however, the biological role of these interactions has not been well investigated. Here, we demonstrated that inhibition of LPA 1 attenuated LPS-induced signaling pathways of phosphorylation of p38 MAPK and I-kB; however, reduction of LPA levels by overexpression of LPP1 had no effects on LPS-induced signals, indicating that LPA 1 -mediated LPS signaling is independent on its LPA-LPA 1 signaling axis in cell culture conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show here that CD14-neutralizing antibody attenuates LPSinduced signal transduction in MLE12 cells. Recent studies demonstrated that, in addition to LBP, CD14 interacted with other proteins, such as surfactant A (32), C (2), and D (32), integrin-␤ 1 (22), and Mac-1 (27); however, the biological role of these interactions has not been well investigated. Here, we demonstrated that inhibition of LPA 1 attenuated LPS-induced signaling pathways of phosphorylation of p38 MAPK and I-kB; however, reduction of LPA levels by overexpression of LPP1 had no effects on LPS-induced signals, indicating that LPA 1 -mediated LPS signaling is independent on its LPA-LPA 1 signaling axis in cell culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…CD14 is known to be expressed in lipid rafts, which are plasma membrane microdomains that are enriched for cholesterol and sphingomyelin and characterized by insolubility in nonionic detergents (8,28). In addition to interaction with LPS, recent studies show that CD14 binds to surfactant proteins (2,4,32) and integrin-␤ 1 (22), suggesting involvement of additional new signaling pathways in CD14-regulated LPS-induced inflammation.…”
mentioning
confidence: 99%
“…A loss of E-cadherin cell-cell contacts is important for single cell invasion and has recently been discovered as a tumor suppressor gene [5]. The α 4 β 1 integrin interacts either with VCAM-1 or CD14 to enhance tumor cell migration or invasion [11, 90]. It has to be ruled out how the interaction of tumor cells and endothelial cells through these receptors might, in turn, alter the mechanical properties of both cell types and change their invasive potential.…”
Section: Interactions Of Tumor Cells and Endothelial Cellsmentioning
confidence: 99%
“…In addition, VLA-4 can serve as a costimulatory molecule and also localizes to the IS of a T-cell-APC conjugate (33), where it may interact with CD14 on the APC (20). Since LFA-1 localization and adhesion to fibronectin require both WAVE2 and the ARP2/3 complex, we next determined whether the localization of this integrin also required these proteins.…”
mentioning
confidence: 99%